Surface-water Interface Induces Conformational Changes Critical for Protein Adsorption: Implications for Monolayer Formation of EAS Hydrophobin - Ley, Kamron; Christofferson, Andrew; Penna, Matthew; Winkler, Dave; Maclaughlin, Shane; Yarovsky, Irene (Frontiers in Molecular Biosciences, 2015)
The class I hydrophobin EAS is part of a family of small, amphiphilic fungal proteins best known for their ability to self-assemble into stable monolayers that modify the hydrophobicity of a surface to facilitate further microbial growth. These proteins have attracted increasing attention for industrial and biomedical applications, with the aim of designing surfaces that have the potential to maintain their clean state by resisting non-specific protein binding. To gain a better understanding of this process, we have employed all-atom molecular dynamics to study initial stages of the spontaneous adsorption of monomeric EAS hydrophobin on fully hydroxylated silica, a commonly used industrial and biomedical substrate. Particular interest has been paid to the Cys3-Cys4 loop, which has been shown to exhibit disruptive behavior in solution, and the Cys7-Cys8 loop, which is believed to be involved in the aggregation of EAS hydrophobin at interfaces. Specific and water mediated interactions with the surface were also analyzed. We have identified two possible binding motifs, one which allows unfolding of the Cys7-Cys8 loop due to the surfactant-like behavior of the Cys3-Cys4 loop, and another which has limited unfolding due to the Cys3-Cys4 loop remaining disordered in solution. We have also identified intermittent interactions with water which mediate the protein adsorption to the surface, as well as longer lasting interactions which control the diffusion of water around the adsorption site. These results have shown that EAS behaves in a similar way at the air-water and surface-water interfaces, and have also highlighted the need for hydrophilic ligand functionalization of the silica surface in order to prevent the adsorption of EAS hydrophobin.